The Effect of Extrinsic Motivation and Organisational Culture on the Performance of Employees at the Perumda Air Minum (PDAM) Tirta Jati Kabupaten Cirebon - Nadila Hikmatusyachdiah; Lisa Harry Sulistiyowati (Universitas KH. Abdul Chalim Mojokerto, 2026)
The aim of this research is to examine how extrinsic motivation and organisational culture partially (t) or simultaneously (f) influence employee performance at Perumda Air Minum Tirta Jati in Cirebon Regency. The sample included of 75 employees, which is referred to as saturated sampling. A questionnaire was used to gather data. The results indicate that extrinsic motivation has a significant positive impact on employee performance, as seen from the t-count value that is greater than the t-table value (3.863 > 1.993), while organisational culture has a positive significant impact, as noted from the t-count value above the t-table value (3.315 > 1.993). Simultaneously, the influence of the extrinsic motivation and organisational culture variables on job efficiency is shown by an F-count exceeding the F-table value, namely 46.568 > 3.12. All results, both partially and collectively, have a significance value less than or equal to 0.05.